Model-Model Kebersamaan Lingkungan: Mewujudkan Persaudaraan Gerejawi - Laksono, Andreas Agung Bowo; Tedjoworo, Hadrianus (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2022)
The Catholic Church in Indonesia views the parochial lingkungan as a community of believers who live in a nearby neighbourhood, practicing fraternity, supporting and enriching one another in their life and ministry. The activities and meetings in the lingkungan are a means for the faithful to establish fraternal relations through shared faith experiences and joint ministries. However, the lingkungan members’ participation in such activities and meetings might decrease due to certain difficulties, and this situation can interfere with the effort of realising their ecclesial communion and fraternity. In this article, the issue of the faithful’s decrease of participation in lingkungan is addressed by offering some models of togetherness inspired by the Scriptures and the Church documents such as Evangelii Gaudium and Fratelli Tutti. The models offered refer to some important aspects as personal encounter, everyday conversation, and sharing of life. Each model explores a different point of view to develop some ways of building togetherness among the faithful in the lingkungan. These models are considered flexible as they can be (re)interpreted according to the relevant challenges and are complementary in their character. Models offered in this article can be seen as alternatives to the existing practices of meeting and catechesis in the parochial lingkungan. They also can help lingkungan administrators and their members participate more actively in realising the ecclesial communion and the Christian fraternity among themselves.